INDICATORS OF MAXIMAL AND EXPLOSIVE STRENGTH OF FIRST-YEAR GYMNASTS AT THE INITIAL TRAINING STAGE (Physical Culture and Sport: Scientific Perspective, 2025)
During the study of specialized literature and based on the experience of training young athletes in technically-aesthetic sports, it was found that in the first year of training, there are differences in the level of preparedness of children, confirmed by research. To establish indicators of maximal and explosive strength of first-year gymnasts at the initial training stage. Theoretical analysis and generalization of scientific and methodological literature data, abstraction, historical method, comparison, pedagogical testing, and methods of mathematical statistics. Tests were used to control the maximal and explosive strength of young gymnasts: "Handgrip Dynamometry," "Standing Long Jump," "Medicine Ball Throw (1 kg) from a seated position," and "Plastic Tennis Ball Throw for Distance." Young gymnasts from the Ivano-Frankivsk Youth Sports School were involved (n=130, including: born in 2018 n=69, 2019 n=45, and 2020 n=19). The analysis of the obtained data showed that the level of preparedness varied among the participants in all aspects. The tests were divided by predominant physical qualities: maximal and explosive strength, strength and speed-strength endurance, coordination qualities, flexibility, and complex manifestations of physical qualities. The analysis indicated a gradual improvement in maximal and explosive strength indicators across all groups from younger to older children. The average test values for handgrip dynamometry were low (11.91 kgf), while the standing long jump showed statistically significant differences between all subgroups. The "Medicine Ball Throw (1 kg) from a seated position" and "Plastic Tennis Ball Throw for Distance" tests also provided important data on the level of physical preparedness of the children. The handgrip strength indicators clearly differentiated the children by birth year, while the standing long jump test reflected differences between all subgroups. These results indicate the necessity of considering individual readiness indicators in the training process of young gymnasts to ensure effective planning of training loads. The analysis of variation coefficients also confirms the need for differentiation of training loads based on individual differences. The indicators of maximal and explosive strength of first-year gymnasts confirmed the importance of individualized approaches in the training process, especially when planning training loads for young athletes of different birth years.
Keywords: young gymnasts; maximal and explosive strength; preparedness; results; differences